SARCASM USED BY NETIZENS ON TWITTER CASE OF ELECTION BIDDEN-TRUMP ERA - Ezra Melita Sitanggang; Tri Wahyu Retno Ningsih (Jurusan Sastra Indonesia, 2022)
Sarcasm is the crudest style of the syndicate language, and its delivery always shows something that is not pleasant to hear. The intent of the research is to discover types of sarcasm from netizens on Twitter during American Election 2020. The data consist of sentences, phrases, and words that contain sarcasm. The researcher uses sarcasm theory of Camp (2011) that secluded into 4 types they are Propositional Sarcasm, Lexical Sarcasm, Like-Prefixed Sarcasm, and Illocutionary Sarcasm to define depicted of sarcasm that used by netizens on Twitter. After analyzing sarcasm on Twitter, the researcher found an amount types of sarcasm they are 22 tweets contain proporsitional sarcasm, 13 tweets contain lexical sarcasm, 5 tweets contain like-prefixed sarcasm, and 10 tweets contain illocutionary. Proporsitional sarcasm becomes dominant type that found out in this research.